Preen oil chemical composition encodes individuality, seasonal variation and kinship in black kites Milvus migrans. (18th July 2018) - Potier, Simon; Besnard, Malicia M.; Schikorski, David; Buatois, Bruno; Duriez, Olivier; Gabirot, Marianne; Leclaire, Sarah; Bonadonna, Francesco
Abstract : Evidence that bird odour can encode social information that can be used in chemical communication is growing, but is restricted to a few taxonomic groups. Among birds, diurnal raptors (i.e. birds from the Accipitriformes and Falconiformes order) have always been considered as mainly relying on their visual abilities. Although they seem to have a functional sense of smell, whether their odour can convey social information has yet to be determined. Combining gas‐chromatography‐mass‐spectrometry (GCMS) and microsatellite data, we tested whether chemical compounds from preen gland secretions can encode sex, age, individuality, seasonal differences and genetic relatedness in the gregarious accipitriform black kite Milvus migrans . While no differences in preen oil composition were found between age classes, an individual signature was detected. While a seasonal variation was found in both sexes, compounds differ between sexes in the non‐breeding season. Finally, a significant correlation between chemical proximity and genetic proximity was detected in male–male dyads and male–female dyads but not in female–female dyads. Our study provides the first evidence in raptors that preen secretion can convey information that may potentially be used in individual recognition, reproductive synchronization and inbreeding avoidance, and suggests that raptors may rely upon their olfactory abilities more than previously thought. This study opens promising avenues for further studies in raptor chemical communication.